Early molecular events associated with liver and colon sub-acute responses to 1,2-dimethylhydrazine: Potential implications on preneoplastic and neoplastic lesion development - Ramos Caetano, Brunno Felipe [UNESP]; Baptista Tablas, Mariana [UNESP]; Ribeiro Romualdo, Guilherme [UNESP]; Marchesan Rodrigues, Maria Aparecida [UNESP]; Barbisan, Luís Fernando [UNESP] (Elsevier, 2020)
This study unveiled the early cellular and molecular events induced by 1,2-dimethylhydrazine (DMH) in the colon and liver and their implications on pre- and neoplastic lesion burden in a late timepoint. Male Wistar rats received four DMH injections (40 mg/kg body weight) for 2 weeks and were sacrificed 24 h (short-term study) or 22 (medium-term study) weeks after the last DMH administration. In the short-term study, DMH led to increased leukocyte (comet assay) and colon (H2AX) genotoxicity, enhanced proliferation (Ki-67) and apoptosis (caspase-3) indexes in both liver and colon. Furthermore, the expression of mRNA (Cat, Gsta1, Gsta2, Gpx1, Gstm1, Sod1, Sod2 and Sod3) and the activity of antioxidant agents were diminished in the colon and liver of DMH-induced rats, eliciting an environment of oxidative stress featuring elevated lipid hydroperoxide levels. Apoptosis effectors were upregulated in the liver (Bax, Casp3 and Fas), and developmental genes were downregulated in both colon and liver (Foxa1, Foxa2, Smad2 and Smad4). In the medium-term study, DMH led to a high number of preneoplastic colonic aberrant crypt foci and tumors (adenomas and invasive adenocarcinomas) but few preneoplastic hepatic glutathione S-transferase (GST-P)-positive foci. Our novel gene expression data highlights overlooked mechanisms in the liver (main metabolizing organ) and colon (main target organ) on toxicity and carcinogenesis induced by repeated doses of DMH, as both organs should be considered in further interventions on the initiation stage of colon carcinogenesis.
Keywords: 1,2-Dimethylhydrazine; Aberrant crypt foci; Antioxidant defense; Colon tumors; Gene expression; GST-P positive preneoplastic foci; Mucin depleted foci